Mümeyyiz Dergisi’ndeki dini motiflerin din eğitimi açısından incelenmesi - Arslan, Yakup (My University, 2007)
MÜMEYYİZ DERGİSİ’NDEKİ DİNÎ MOTİFLERİN DİNİ EĞİTİM AÇISINDAN İNCELENMESİ Bu çalısma iki ana bölümden olusmaktadır. lk bölümde çocuk edebiyatının önemli gördügümüz tanımları ile Dünya’da ve Türkiye’deki tarihi gelisim seyrini ele aldık. Ayrıca Tanzimat’ın ilanından sonra yayınlanan çocuk dergilerinin dikkate deger görülenlerden bazılarını kısaca tanıtmaya çalıstık. Bu bölümün sonunda tezimizi hazırlarken kullandıgımız temel kaynagın incelenmesi yer almaktadır. kinci bölümde ise Mümeyyiz Dergisi’ndeki dinî motifler isledikleri konulara göre din egitimi ile iliskilendirilerek tasnif edilmistir. Bu bölümde dergilerde yer alan dinî motiflerin tamamı incelenmis, fakat bunlardan önemli görülenler degerlendirilmeye tabi tutulmustur. Çalısmamızın amacı Mümeyyiz Dergisindeki dinî motiflerin din egitimi açısından incelenip günümüz din egitimine yapacagı katkıları ortaya koymaktır.

THE ANALYSIS OF THE RELIGIOUS MOTIVES IN MÜMEYYİZ MAGAZINE IN THE SENCE OF RELIGIOUS EDUCATION This study is formed of two parts. At the first part of the study we have worked on The worlds and Türkey’s developing history and the definitions which have been found to be important at children literature. Aport from that we have tried to explain in short, the children periodicals that have been puplished after Tanzimat (The political reforms made in the ottoman state in 1839.) and have gathered a great lot of attention. At the end of this part there is the study of the main source which we have used while we were getting the study done. At the second part of our study, the religious motifs in Mümeyyiz periodical has been related with the religious education and has been classified together. At this part of the study all the religious motifs in the periodicals have been found important has been taken into cansideration. Our studies objectives are to study the religious motifs in Mümeyyiz periodical with in casideration of the religious education and put out the assistance for todays relicious education.
Keywords: Din Eğitimi; İlköğretim_Din Eğitimi; Süreli Yayınlar_Din Eğitimi